SAFETY OF OFF-PUMP CORONARY ARTERY BYPASS GRAFTING IN PATIENTSWITH ACUTE CORONARY SYNDROME - I. . Sharipov; R. . Yarbekov; A. . Ismatov; M. . Muradov; S. . Omonov; T. . Vakhidov (Евразийский Кардиологический Журнал)
Conventional on-pump coronary artery bypass surgery (CABG) in patients with acute coronary syndrome (ACS) is associated with higher risk of complications and mortality. There is a lack of data on results of off-pump CABG operations (being popularised in the last 2 decades) in such a group of high-risk patients. The aim of the study was to assess feasibility and results of off-pump CABG operations in patients with ACS.